2019
DOI: 10.1155/2019/2097415
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Consumer Food Preferences: Food Taste and Depression-Based Evoked Emotional Expressions with the Use of Face Reading Technology

Abstract: In this study, several factors (social status, age, gender, education, knowledge about healthy eating, and attitude to food) affecting consumer food choices (FC), including the relationship between the taste of food, FC, and depression, were analysed by using sensory traits and face reading technology. The first stage of the experimental scheme was the analysis of factors affecting consumer food preferences by using a questionnaire, while the second stage was evaluation of emotional expressions evoked by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 37 publications
3
41
0
1
Order By: Relevance
“…Young adults, women, residents in Brazil or Argentina, those who live in rural areas, those who are single or divorced, those who have secondary education, or whose area of study or work is related with nutrition, psychology, food or health are the ones that evidence a higher degree of conditioning in their eating behaviour according to emotional aspects. These results are, to some extent, in line with those of the research by Bartkiene et al [ 48 ], which indicated that age, education level and sex are associated with emotional motivations for eating. The works by Bennett et al [ 46 ] and Guiné et al [ 49 ] also reported gender differences in the emotional factors driving eating behaviour.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Young adults, women, residents in Brazil or Argentina, those who live in rural areas, those who are single or divorced, those who have secondary education, or whose area of study or work is related with nutrition, psychology, food or health are the ones that evidence a higher degree of conditioning in their eating behaviour according to emotional aspects. These results are, to some extent, in line with those of the research by Bartkiene et al [ 48 ], which indicated that age, education level and sex are associated with emotional motivations for eating. The works by Bennett et al [ 46 ] and Guiné et al [ 49 ] also reported gender differences in the emotional factors driving eating behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…According to literature, a more personalized analysis is required in the design of proposals that aim to promote adherence to healthy eating behaviours [ 48 ]. Decision-makers and professionals responsible for organizing health-promoting initiatives should therefore seek to increase citizens’ food literacy levels and address the diversity of individual variables, such as sex, age, education level, living environment and culture of origin, in the design of training proposals, in order to undertake more effective actions in adhering to behaviours that contribute to the health and well-being of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The beverage prototypes were also tested by applying FaceReader 6.0 software (Noldus Information Technology, Wageningen, The Netherlands) ( Figure 1 ), with a scoring scale of 8 emotion patterns (neutral, happy, sad, angry, surprised, scared, disgusted, contempt) according to Bartkiene et al (2019) [ 27 ]. The whole procedure was filmed using a Microsoft LifeCam Studio webcam mounted on a laptop facing the participants, and Media Recorder (Noldus Information Technology) software.…”
Section: Methodsmentioning
confidence: 99%
“…The major determinant of food choice is hunger; however, in the presence of different food options, the choice of what we eat is not determined solely by physiological or nutritional needs. Gender, age, education level, and emotional motivations should also be taken into account [1]. In addition, taste perception and food hedonics are also important determinants in such choices [2][3][4].…”
Section: Introductionmentioning
confidence: 99%